2018
DOI: 10.3390/en11010124
|View full text |Cite
|
Sign up to set email alerts
|

Evolving Microbial Communities in Cellulose-Fed Microbial Fuel Cell

Abstract: Abstract:The abundance of cellulosic wastes make them attractive source of energy for producing electricity in microbial fuel cells (MFCs). However, electricity production from cellulose requires obligate anaerobes that can degrade cellulose and transfer electrons to the electrode (exoelectrogens), and thus most previous MFC studies have been conducted using two-chamber systems to avoid oxygen contamination of the anode. Single-chamber, air-cathode MFCs typically produce higher power densities than aqueous cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 69 publications
2
26
0
Order By: Relevance
“…Parabacteroides played an important role in DIET, producing the essential VFA required by the exoelectrogenic bacteria to degrade and donate electrons to electrotrophic methanogens. Parabacteroidetes growth has been reported in microbial fuel cells [80], assuming the same role as in this study, however it has not been reported in studies that are related with the promotion of DIET in anaerobic reactors. This is a result of the fact that most of these studies employ synthetic wastewater that is easily converted to methane.…”
Section: Microbial Analysissupporting
confidence: 79%
“…Parabacteroides played an important role in DIET, producing the essential VFA required by the exoelectrogenic bacteria to degrade and donate electrons to electrotrophic methanogens. Parabacteroidetes growth has been reported in microbial fuel cells [80], assuming the same role as in this study, however it has not been reported in studies that are related with the promotion of DIET in anaerobic reactors. This is a result of the fact that most of these studies employ synthetic wastewater that is easily converted to methane.…”
Section: Microbial Analysissupporting
confidence: 79%
“…In the case of complex substrates, such as wastewater, microbial consortia need to be used. In such consortia there are fermentative and methanogenic species that decompose complex substances into simple organics that can be further used by electrogenic species for current production [17]. MFCs were successfully applied in the treatment of various types of wastewater (including industrial) with the use of dual-chamber and single-chamber reactors [18].…”
Section: Reference [4]mentioning
confidence: 99%
“…Inflammation is our natural reaction to injury, but when this reaction is too intense, it can lead to several diseases, including arthritis and asthma. In fact, the more inflammation in the body is, the more likely it is for heart disease and atherosclerosis (Toczyłowska-Mamińska et al, 2018 ). According to a previous study, one of the ways to reduce inflammation in the body is the presence of beneficial bacteria in the intestine.…”
Section: The Role Of Microbium In Reducing Heart Diseasementioning
confidence: 99%